Prostitution Phenomena Reflected at Haruki Murakamiâs After Dark Novel (2007): A Feminist Approach. Research Paper Muhammdiyah University of Surakarta 2015 - Septiyani, Rosanti Dwi; Candraningrum, Dewi; Setyabudi, Titis (JoLLIET, 2015)
The major problem in this research is the existance of prostitution phenomena in Japan as reflected in Haruki Murakamiâs After Dark novel. The research analyses Haruki Murakamiâs After Dark novel to find out the structural elements of the novel, and also to understand the existence of prostitution phenomena in modern Japanese society based on feminist approach. In analysing the novel, the reseacher uses qualitativea method. The data are divided into two kinds data, namely primary data and secondary data. The primary data sources is the novel entitled After Dark by Haruki Murakami which is published in 2007. And the secondary data is the sources which is related to the issue taken by reseacher, such as the book of the theory namely feminism approach and other resources about Japanese society during in the early of twenty one century.The method of getting data is library research. However the descriptive analysis is the technique of data analysis. The outcome of the study draws the following conclusions. Firstly, the existence of prostitution phenomena in modern Japan society is placing women in the second position under the man. Secondly, there are four factors that involve the existence of prostitution in Japan .They are the men who buy commercial sex acts, the exploiters who make up the sex industry, the states that are destination countries, the culture that tolerates or promotes sexual exploitation. It also reveals the perception of Japanese society about sex which is changing following the modernity and making sex not taboo anymore.